Effects of light-emitting diodes on cell biology - Veloso, Tatiane Moraes; de Souza da Fonseca, Adenilson; Costa dos Santos, Gilson (Frontiers in Photonics, 2022)
Currently, light-emitting diodes (LEDs) are considered a substitute for low-power lasers in phototherapy protocols. LEDs enable photobiomodulation on biological tissues and are considered safe and economical. However, the molecular and metabolic mechanisms involved in LED-induced photobiomodulation are not yet fully understood. This review summarizes the metabolic mechanisms involved in LED-induced photobiomodulation in biological tissues under different irradiation parameters and conditions. Studies on LED-induced metabolism photobiomodulation were accessed using scientific article databases, whose findings were summarized in terms of molecular and cellular mechanisms. Data from the accessed studies suggested that the molecular mechanism of LED-induced photobiomodulation involves photoacceptors, such as cytochrome C oxidase, membrane ion channels, mitochondrial modulation, and the production of ROS.